1984
DOI: 10.1007/bf02408553
|View full text |Cite
|
Sign up to set email alerts
|

Imitating the autistic child: Facilitating communicative gaze behavior

Abstract: The nonverbal autistic child exhibits a persistent and characteristic feature known as gaze aversion. Since gaze interaction between the autistic child and the clinician [or adult] is a requisite experience in therapeutic learning, procedures that modify gaze behavior in autistic children serve an important clinical function. The present research was designed to investigate three kinds of adult-child interaction that differentially affected changes in gaze behavior. The interaction procedure in which the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 7 publications
2
36
0
1
Order By: Relevance
“…Tiegerman and Primavera (1981) had an experimenter who imitated manipulating the same object in response to children manipulating an object; that is, the performances between children and the experimenter were similar in the manipulation of the same object, the action on the object, and the interaction time with the object. Results showed that adults' imitation of young children with ASD is potentially effective in helping these children to initiate gaze interaction with adults, which also has been confirmed in other studies (e.g., Dawson & Adams, 1984;Tiegerman & Primavera, 1984). To further investigate the effects of adult imitating children with ASD, early work on imitation prompted Nadel et al (2000) to use the adapted still-face (SF) paradigm (Tronick, Als, Adamson, Wise, & Brazelton, 1978).…”
mentioning
confidence: 88%
“…Tiegerman and Primavera (1981) had an experimenter who imitated manipulating the same object in response to children manipulating an object; that is, the performances between children and the experimenter were similar in the manipulation of the same object, the action on the object, and the interaction time with the object. Results showed that adults' imitation of young children with ASD is potentially effective in helping these children to initiate gaze interaction with adults, which also has been confirmed in other studies (e.g., Dawson & Adams, 1984;Tiegerman & Primavera, 1984). To further investigate the effects of adult imitating children with ASD, early work on imitation prompted Nadel et al (2000) to use the adapted still-face (SF) paradigm (Tronick, Als, Adamson, Wise, & Brazelton, 1978).…”
mentioning
confidence: 88%
“…Improvements in social behaviors and imitation abilities have been shown when adults imitate children with ASD (Tiegerman and Primavera 1984;Dawson and Adams 1984;Nadel et al 2000;Heimann et al 2006). Nadel et al (2000) examined whether using a still-face paradigm and contingent imitation in children with ASD would increase their social initiations.…”
Section: Using Imitation To Increase Social Interactionsmentioning
confidence: 99%
“…Gaze following task According to the description of Phillips et al (1995). Imitation task 2 Task based on the task developed by Tiegerman and Primavera (1984), using the following five objects; spoon, car, tiny doll, hairbrush, castagnettes, where the child is invited to imitate the experimenter. Imitation/cognition task The child has to activate a toy after the demonstration of the experimenter.…”
Section: Imitation Taskmentioning
confidence: 99%